2023
DOI: 10.1186/s12983-023-00483-2
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and functional analysis of the molting gene CYP302A1 of Daphnia sinensis

Abstract: Background Molting is an important physiological process in the growth and development of arthropoda, which is mainly regulated by juvenile hormone and ecdysone. CYP302A1 is a key enzyme which plays a critical role in the synthesis of ecdysone in insects, but it has not been identified in cladocera. Results The CYP302Al gene of Daphnia sinensis was cloned and its function was analyzed in this paper. The CYP302Al gene of D. sinensis was 5926 bp in f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Genomic presence of dib (cyp302a1) as well as sad (cyp315a1) was confirmed in all the four major arthropod groups, except for Ixodes scapularis (Qu et al, 2015;Schumann et al, 2018;Miyakawa et al, 2018;Rotenberg et al, 2020;Dermauw et al, 2020;Qi et al, 2023). Similarly, shd (cyp314a1) was found in most examined arthropods, and was even cloned from Daphnia pulex and L. salmonis, except for the decapods Neocaridina denticulata, Litopenaeus vannamei, Penaeus monodon and Palaemon carinicauda (Sumiya et al, 2014;Qu et al, 2015;Sandlund et al, 2018;Ventura et al, 2018;Dermauw et al, 2020).…”
Section: (1) Ecdysteroid Biosynthesis Toolkits Comprise Stable and Dy...mentioning
confidence: 80%
“…Genomic presence of dib (cyp302a1) as well as sad (cyp315a1) was confirmed in all the four major arthropod groups, except for Ixodes scapularis (Qu et al, 2015;Schumann et al, 2018;Miyakawa et al, 2018;Rotenberg et al, 2020;Dermauw et al, 2020;Qi et al, 2023). Similarly, shd (cyp314a1) was found in most examined arthropods, and was even cloned from Daphnia pulex and L. salmonis, except for the decapods Neocaridina denticulata, Litopenaeus vannamei, Penaeus monodon and Palaemon carinicauda (Sumiya et al, 2014;Qu et al, 2015;Sandlund et al, 2018;Ventura et al, 2018;Dermauw et al, 2020).…”
Section: (1) Ecdysteroid Biosynthesis Toolkits Comprise Stable and Dy...mentioning
confidence: 80%
“…JH regulates vitellin synthesis, oocyte maturation, and the uptake of ooxanthine by oocytes [ 41 ]. 20E, a steroid hormone synthesized and secreted by the insect’s prothoracic gland, is vital for regulating growth, development, metabolism, and reproduction [ 42 ]. In our study, we found that the non-consumptive effect of natural enemies resulted in reduced levels of JH, 20E, and vitellogenin.…”
Section: Discussionmentioning
confidence: 99%
“…Molting plays an extremely important role in the growth, development, reproduction, and survival of crustaceans and runs through their entire life cycle [ 10 ]. During the breeding period, female molting is interwoven with ovarian development, specifically manifested in the need to molt before holding eggs [ 11 ].…”
Section: Introductionmentioning
confidence: 99%